A pharmacology primer : theory, applications, and methods - Kenakin, Terrence P. (Elsevier Academic Press, 2006)
The Second Edition will continue this tradition of better preparing researchers in the basics of pharmacology. In addition, new human interest material including historical facts in pharmacology will be added. A new section on therapeutics will help readers identify with diseases and drug treatments. *Over 30 new figures and tables *More human interest information to provide readers with historical facts on pharmacology research *New section on therapeutics to help identify diseaes and drug treatments *New section on new biological concepts relevant to pharmacological research (i.e., systems biology) *New study sections organized with ASPET and other international pharmacology organizations *New coverage of pharmacokinetics and drug disposition.